Using bio-optical parameters as a tool for detecting changes in the phytoplankton community (SW Portugal) - Goela, Priscila (2018)
Upwelling events off the Southwest coast of Portugal can trigger phytoplankton blooms that are important for the fisheries and aquaculture sectors in this region. However, climate change scenarios forecast fluctuations in the intensity and frequency of upwelling events, thereby potentially impacting these sectors. Shifts in the phytoplankton community were analysed from the end of 2008 until the beginning of 2012 by examining the bio-optical properties of the water column, namely the absorption coefficients for phytoplankton, non-algal particles and coloured dissolved organic matter (CDOM). The phytoplankton community was assessed by microscopy, with counts from an inverted microscope, and by chemotaxonomic methodologies, using pigment concentrations determined by High-Performance Liquid Chromatography (HPLC). Results both from microscopy and from chemotaxonomic methods showed a shift from diatom dominance related to bloom conditions matching upwelling events, to small flagellate dominance related to no-bloom conditions matching relaxation of upwelling. During bloom conditions, light absorption from phytoplankton increased markedly, while non-algal particles and CDOM absorption remained relatively constant. The dynamics of CDOM in the study area was attributed to coastal influences rather than from phytoplankton origin. Changes in phytoplankton biomass and consequent alterations in phytoplankton absorption coefficients were attributed to upwelling regimes in the area. Bio-optical parameters can contribute to environmental monitoring of coastal and oceanic waters, which in the case of the European Union, involves the implementation of the Water Framework, Marine Strategy Framework and Marine Spatial Planning Directives. (C) 2015 The Authors.Published by Elsevier Ltd.